Sirolimus Restores Erythropoiesis and Controls Immune Dysregulation in a Child With Cartilage-Hair Hypoplasia: A Case Report - Del Borrello, Giovanni; Miano, Maurizio; Micalizzi, Concetta; Lupia, Michela; Ceccherini, Isabella; Grossi, Alice; Cavalli, Andrea; Gustincich, Stefano; Rusmini, Marta; Faraci, Maura; Dell’Orso, Gianluca; Ramenghi, Ugo; et al. (Frontiers in Immunology, 2022)
Cartilage-hair hypoplasia (CHH) is a syndromic immunodeficiency characterised by metaphyseal dysplasia, cancer predisposition and varying degrees of anemia. It may present as Severe Combined Immunodeficiency in infancy, or slowly progress until fully manifesting in late adolescence/adulthood. No targeted treatment is currently available and patients are usually managed with supportive measures, or are offered bone marrow transplant if the clinical phenotype is severe and a suitable donor is available. We report the case of a young girl presenting with transfusion-dependent erythropoietic failure and immunological features resembling Autoimmune Lymphoproliferative Syndrome who responded well to empirical sirolimus. She later developed a marked growth delay, which was ultimately attributed to metaphyseal dysplasia. A diagnosis of CHH was reached through Whole Genome Sequencing (WGS), after less sensitive genetic diagnostic strategy failed. The patient eventually underwent an haplo-identical bone marrow transplant due to progressive combined immunodeficiency manifested as cryptococcal meningoencephalitis. This case illustrates the potential role of sirolimus in correcting anemia and partially controlling the immune aberrations associated with CHH, and serves as a reminder of the invaluable role of WGS in diagnosing patients with complex and atypical presentations.